Enhanced enzymatic degradation resistance of plasmid DNA in ionic liquids1. Issue 54 (13th June 2015) - Mazid, Romiza R.; Cooper, Alexandra; Zhang, Ying; Vijayaraghavan, R.; MacFarlane, Douglas R.; Cortez-Jugo, Christina; Cheng, Wenlong
<x xml:space="preserve">Abstract</x> Buffered ionic liquids can substantially enhance enzymatic degradation resistance of plasmid DNA, indicating the potential to serve as next-generation biological storage buffer at ambient temperature.